Assisted heat transfer enhancement in non-Newtonian dielectric fluids based on ion conduction phenomena - Chen, Di-Lin (2024)
Electric field-assisted technologies show prospects for heat removal in electronic cooling scenarios with electro-thermo-convection phenomena. The coupled multiphysics field model is built using the finite volume method, and two configurations (depending upon the orientation of the electric field and gravity) are investigated for different shear-thinning properties and polymer elasticities. The results demonstrate a remarkable impact on the heat exchange efficiency, energy budget, plume morphology, and force distribution features. Two key partitions (buoyancy or Coulomb force-dominated regions) can be divided by Rayleigh number Ra ≤ 103 and electric Reynolds number R e E ≤ 1.57. A heat transfer boost of 13.9 times and 5.0 times was obtained in the two arrangements vs no electric reinforcement. The shear-thinning shows a noticeable positive contribution, and the heat transfer efficiency can be modulated by polymer elasticity within a wide parameter range. A detailed evaluation of the interfacial forces reveals the nonmonotonic curves of fluid convection and energy inputs.